Biodiversity management plan in the non-conservation area, Cisokan hydropower plan area, Cianjur, West Java, Indonesia - TEGUH HUSODO; SYA SYA SHANIDA; ERRI NOVIAR MEGANTARA (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Husodo T, Shanida SS, Megantara EN. 2019. Biodiversity management plan in the non-conservation area, Cisokan hydropower plan area, Cianjur, West Java, Indonesia. Biodiversitas 20: 1524-1536. Based on data from various environmental studies at the Upper Cisokan Pumped Storage (UCPS) Hydropower plan area, further studies need to be carried out that can provide clearer guidance on how to protect and restore the environment (including habitat) around the UCPS, protect, and manage the endangered biodiversity through adaptive approaches and ecosystem management. One of these studies was the UCPS Biodiversity Management Plan (BMP). The aim of this study was to identify the strategy for biodiversity management at the project site. Methods of this study were based on several years of qualitative and descriptive-analytical studies, which updated information from earlier studies. Information on the area’s biodiversity was obtained directly through field surveys and indirectly through semi-structured interviews and focus group discussions (FGD) with local community members and other stakeholders in the area. This article presents the strategy for biodiversity management at project site, including minimizing habitat gap and habitat loss; expanding and enriching habitats; making corridors; protecting the natural forests (protection of remnant forest); controlling access; managing fire, the impact of traffic on native fauna, land clearing and human-wildlife conflict; minimizing impacts to biodiversity,  particularly threatened species; integrating management with adjoining land managers (PLN, perhutani, the community); strengthening capacities for integrating and institutionalizing biodiversity conservation and management; conducting campaign for biodiversity awareness, communication, and education; and developing value-added products and alternative sustainable livelihood for bio-resource-dependent communities. Keywords: Biodiversity Management Plan, Hydropower Company